HUBUNGAN ANTARA KESADARAN METAKOGNITIF DENGAN KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI SUHU, KALOR, DAN PEMUAIAN - Maftuhatul Qolbiyah Munasik; Maria Chandra Sutarja; Nur Qomaria; Wiwin Puspita Hadi; Sunu Wahyudhi (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2026)
The purpose of this study is to examine the relationship between metacognitive awareness and students' problem-solving abilities in the subjects of temperature, heat, and expansion. This is a quantitative study using a correlational survey method. The study was conducted at SMP Islam Blega with a sample size of 103 seventh-grade students. Data collection utilized the MAI (Metacognitive Awareness Inventory) questionnaire for metacognitive awareness and problem-solving test questions for problem-solving ability. Data analysis employed the Spearman correlation test. The results of the study showed that the significance value was 0.000 kurang dari 0.05 with a correlation coefficient of 0.469, which means that there is a positive correlation between metacognitive awareness and students' problem-solving skills. The coefficient of determination was 0.277, meaning that the influence of metacognitive awareness on students' problem-solving ability in the subject matter of temperature, heat, and expansion was 27.70%.